Kasus Rokok Tanpa Pita Cukai Dan Pertanggungjawaban Pidana (Studi KPPBC Tipe Madya Pabean C Magelang) - Loren, Dinda Ayu Rosa; Basri, B; Krisnan, Johny; Kurniaty, Yulia (Prosiding University Research Colloquium, 2023)
Cigarettes are one source of state revenue received from the imposition of excise. However, it turns out that there are also cigarettes that do not have excise bands (plain). Cigarettes are one of the goods that are subject to excise duty because they are considered to be an item in which it is necessary to monitor their distribution, control their consumption, and in their use can cause a negative impact on the wearer or the community and the environment. This study aims to further examine the circulation of cigarettes without excise stamps in the prosecution area of KPPBC TMP C Magelang. This research uses a normative-empirical method which is a legal research study regarding the implementation or enactment of normative legal provisions. Circulation of cigarettes without excise stamps is very detrimental to the state, it is necessary to know about the parties involved in their circulation and the factors that become obstacles in enforcing cases of cigarettes without excise stamps.